2007
DOI: 10.1021/jo062578i
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Di(4-halophenyl)nitrenium Ions:  Nucleophilic Trapping, Aromatic Substitution, and Hydrogen Atom Transfer

Abstract: The reactive intermediates N,N-di(4-chlorophenyl)nitrenium ion and N,N-di(4-bromophenyl)nitrenium ion were generated through photolysis of the corresponding N-amino(2,4,6,-collidinium) ions. The behavior of these diarylnitrenium ions was characterized by laser flash photolysis, analysis of the stable photoproducts, and ab initio calculations with density functional theory. The latter predict these species to have singlet ground states. The halogenated diarylnitrenium ions are significantly longer lived than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 50 publications
9
36
1
Order By: Relevance
“…In fact, this signalpersists for over 500 μs, and consequently it is not possible to provide a specific lifetime given the constraints of the experimental set up. The 720 nm transient has been observed in other experiments involving LFP of 1 and has been attributed to radical cation 3 10. Indeed, this absorption maximum is consistent with other reports where 3 has been generated by other routes.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In fact, this signalpersists for over 500 μs, and consequently it is not possible to provide a specific lifetime given the constraints of the experimental set up. The 720 nm transient has been observed in other experiments involving LFP of 1 and has been attributed to radical cation 3 10. Indeed, this absorption maximum is consistent with other reports where 3 has been generated by other routes.…”
supporting
confidence: 91%
“…Earlier studies 10,12 demonstrated that N,N-di (4-bromophenyl) for >500 μs in water and does not react at an observable rate with any added nucleophiles. These experiments support the original assignment of the 720 nm signal to the radical cation, rather than the nitrenium dication.…”
Section: Introductionmentioning
confidence: 99%
“…Because singlet arylnitrenium ions have been implicated in carcinogenesis, [34][35][36][37][38][39] the study of the influence of substituents on the relative energies of the singlet and triplet states of such systems has been a topic of considerable theoretical interest. [40][41][42][43][44][45][46] In this context, Sullivan et al [44] have previously computed linear correlations against s and s þ values for several actual functional groups and reported optimal linear correlation with the latter scale at the BPW91/cc-pVDZ level of theory (including thermal free-energy contributions and aqueous solvation effects with the SM5.42R continuum solvation model [47] ). We observed similarly good correlations with s þ values for the levels of theory employed here, with gas-phase r 0 values of about À5.0.…”
Section: Resultsmentioning
confidence: 99%
“…Falvey and coworkers [10,11,12,13] reported several works on the chemical and spectroscopic behavior of the N , N -diphenylnitrenium ion ( 1 ) formed after photoexcitation of the 1-( N , N -dipheylamino)-2,4,6-triphenylpyridinium ion (see Scheme 1), and this aryl nitrenium ion was proven to have a ground state singlet character with some overlap between an unfilled nitrogen based p -orbital with filled π-orbitals on the phenyl groups [12,14]. Furthermore, Thomas and Falvey’s research work showed that the N , N -di(4-bromophenyl)nitrenium ion ( 2 ) formed after photoexcitation of N -(4,4′-dibromodiphenylamino)-2,4,6-trimethylpyridinium BF 4 − salt (DN) had greater stability with a longer lifetime than the unsubstituted nitrenium ion 1 , which was revealed by study of laser flash photolysis to have a lifetime of 124 µs in MeCN, and 6.57 µs in water [10]. Macernis et al, studied the effect of surrounding polar environments on the molecular behavior of the related nitrogen [15].…”
Section: Introductionmentioning
confidence: 99%